Penerapan Good Governance Melalui Electronic Government (Studi Pada Media Center Pemerinah Kota Surabaya) - Dwi Ardian Heryudho (Jurnal Administrasi Publik, 2013)
Abstract:Â  The Implementation of Good Governance through Electronic Government. The globalization era which is coming fast and the information technology that is develop rapidly, demanding the government to do bureaucracy reformation by turning into E-government paradigm, for the sake of forming the Good Governance. The purpose of this study is to know and to analyze the implementation of Good Governance principle through the implementation of media center and also the other factors which are affecting the implementation of Good Governance principle through media center. This study is a descriptive study by using qualitative approach.The result of this study showed that the implementation of media center can form the Good Governance principle such as effectiveness and efficiency, transparency, responsiveness also participation. Keywords: Good Governance, Electronic Government, Media Center Abstrak: Penerapan Good Governance Melalui Electronic Government. Era globalisasi yang datang begitu cepat, serta kemajuan teknologi informasi yang pesat menuntut pemerintah untuk melakukan reformasi birokrasi dengan beralih pada paradigma E-government, demi mewujudkan pemerintahan yang baik (Good governance).Penelitian ini bertujuan untuk mengetahui dan menganalisis penerapan prinsip-prinsip Good governance melalui pelaksanaan media center, serta faktor-faktor yang mempengaruhi penerapan prinsip-prinsip good governance melalui media center. Jenis penelitian yang digunakan adalah jenis penelitian deskriptif dengan pendekatan kualitatif.Hasil penelitian menunjukkan bahwa pelaksanaan media center dapat mewujudkan prinsip-prinsip good governance seperti prinsip efektifitas dan efisiensi, transparansi, responsif serta partisipasi. Kata Kunci: Good Governance, Electronic Government, Media Center